Anthropological Component of Descartes’ Ontology - Anatolii M. Malivskyi (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose of the article is to outline and comprehend the Descartes’ theory about anthropological component of ontology as the most important part of his philosophy. The accomplishment of this purpose covers the successive solution of the following tasks: 1) review of the research literature concerning the problem of human’s presence and the individual nature of truth; 2) emphasize the ambivalence of the basic intention of his legacy; 3) justify the thesis about constitutivity of human’s presence and comprehend passions as the form of disclosure of ontology’s anthropological component. Methodology. The use of the euristic potential of phenomenology, postpositivism and postmodernism makes it possible to emphasize the multiple-layer and multiple-meaning classical philosophy works, to comprehend the limitation and scarcity of the naïve-enlightening vision of human nature and to look for a new reception of European classics that provides the overcoming of established nihilism and pessimism concerning the interpretation of human nature. Scientific novelty. It is the first time that anthropological component of Descartes’ ontology became an object of particular attention. It previously lacked attention because of following main reasons: 1) traditional underestimating of the fact of Descartes’ legacy incompleteness as an unrealized anthropological project and 2) lack of proper attention to the individual nature of truth. The premise for its constructive overcoming is the attention to ambivalence of the basic intention and the significance of ethics in the philosopher’s legacy. His texts and research literature allow confirming the constitutive nature of human’s presence and passions as the key form of disclosure of the ontology anthropological component. Conclusions. The established tradition of interpretation the Descartes’ philosophizing nature as the filiation process of impersonal knowledge loses its cogency these days. The unprejudiced vision of the texts urges to revise (1) the interpretation of cognition process as reflection, (2) the vision of philosophizing process as the depersonalized one, and (3) reduced human image as a thinking thing as unacceptable.